Analisis Penempatan Transformator Distribusi Berdasarkan Drop Voltage Pada PT. PLN (Persero) Distribusi Lamongan Menggunakan Software Etap 19.0 - Ali Mahfud Shodar (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
The need for electrical energy from year to year influences the need for electrical energy at every level of the general public and industry as electricity users. Because electricity has become a part of life (Roza, 2019). In this case, there are separate challenges that must be faced by every company operating in the electricity supply sector, especially the State Electricity Company (PLN), which is the sole company in serving electrical energy needs. The power generation centers are far from the load center, this results in quite large losses in the distribution of electric power. So, when distributing electrical power through transmission and distribution, voltage drops will occur along the line. The length of the distribution channel from the substation to the distribution transformer or from the distribution transformer to the load (Roza, 2019).